Maastricht. Zwitsers vernuft in een achttiende-eeuwse grensstad - Beckers, Remco (Wereldsteden van de Lage Landen. Stadsgeschiedenis van Nederland en België, 2025)
Keywords: Ausländischer Arbeitnehmer; Maastricht; Migration; Schweiz; Stadt; Stuckateur

Les écarts de revenus dans les espaces transfrontaliers. Des moteurs de la mobilité transfrontalière - Belkacem, Rachid (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „This article analyses wage disparity in cross-border spaces in the Greater Region (GR) and Upper Rhine. It is based on the results of two studies, the first funded by EURopean Employment Services-Greater Region (EURES-GR) in 2022 and the other, ongoing, funded by EURopean Employment Services-T Upper Rhine. The analysis shows that this disparity can be explained by various economic, sociological and institutional factors, which operate on various levels: micro (relating to corporate policies), macro (relating to national taxation and social security policy) and meso (relating to economic sectors and branches). It begins by showing that salaries and their various component parts are hard to define, making cross-border comparison difficult. It then signals that while wages in Switzerland and Luxembourg are very attractive, they must be balanced against the cost of living and working hours, which differ on each side of the border. The main takeaway from this analysis is that the gap between wages and the cost of living is a significant driver of cross-border working in border regions.“
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Lohnniveau; Mobilität; Schweiz; Wohnen; Wohnungsmarkt

Le travail frontalier au Luxembourg et en Suisse. Similitudes, différences et défis communs - Pigeron-Piroth, Isabelle; Wille, Christian (Les travailleurs frontaliers au Luxembourg et en Suisse. Emploi, Quotidien et Perceptions, 2019)
Keywords: Grenzarbeitnehmer; Schweiz